The Model Processing Research in PRO/E and ADAMS Co-simulation. (February 2019) - Li, Xurong
Abstract: This paper discusses the specific methods of operation and some skills when the model is imported from PRO/E to ADAMS, Meanwhile a basic principle is pointed out. That is the parts involved in moving should be finished in ADAMS as much as possible, the parts that do not participate in moving with high appearance requirements as much as possible are modeled in PRO/E. The methods, principles and techniques of this paper have guiding significance in practice for the engineers.